Kajian Potensi Senyawa Aktif Bahan Alam sebagai Inhibitor Human Epidermal Growth Factor Receptor 2 (Her-2) pada Kanker Payudara : Kajian Penambatan Molekuler - Saeful Amin; Anantha Puspatiara; Fina Awaliah; Widiya Zulvania (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Breast cancer is the most prevalent type of cancer in women worldwide, with approximately 2.3 million new cases or 11.7% of all cancer cases. Human Epidermal Growth Factor Receptor 2 (HER-2) is one of the important therapeutic targets in breast cancer that is overexpressed in 15-25% of cases. Conventional cancer treatments such as chemotherapy often cause adverse side effects, so safer alternative therapies are needed. This study aims to assess the potential of active compounds from medicinal plants as HER-2 inhibitors through a molecular docking approach. The literature review method was used by analysing related research articles in the last five years obtained from PubMed and Google Scholar databases. The results showed that several active compounds have high potential as HER-2 inhibitors, including beta cystosterol from guava leaves (Psidium guajava L.) with a binding energy value of -12.3 kcal/mol, vitexin from dandang gendis (Clinacanthus nutans L.) with a value of -9.3 kcal/mol, and isovitexin from basil mekah (Ocimum gratissimum) with a value of -9.11 kcal/mol. These findings provide a basis for further development of natural active compounds as potential breast anticancer drug candidates with minimal side effects.